If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 62 + -3x = 10 + 23x Solving 62 + -3x = 10 + 23x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23x' to each side of the equation. 62 + -3x + -23x = 10 + 23x + -23x Combine like terms: -3x + -23x = -26x 62 + -26x = 10 + 23x + -23x Combine like terms: 23x + -23x = 0 62 + -26x = 10 + 0 62 + -26x = 10 Add '-62' to each side of the equation. 62 + -62 + -26x = 10 + -62 Combine like terms: 62 + -62 = 0 0 + -26x = 10 + -62 -26x = 10 + -62 Combine like terms: 10 + -62 = -52 -26x = -52 Divide each side by '-26'. x = 2 Simplifying x = 2
| (8-u)(3u-7)=0 | | 62-3x=10+23 | | 4y+14+5y=50 | | 62-3=10+23 | | x+y^2-c=3x-y+c | | 6(x-6)+9=-27 | | n^2-11n-90=0 | | 18+2-3*4=77 | | 3a-5=9 | | 7n^2-14n-73=9 | | 8n=2(4n+2) | | -3(k-11)=-5(k+5) | | 8(2x-1)-10x+8= | | -0.2+6.66=-0.4x+6.86 | | 12x=23 | | 2x^2+4=-6x | | 5(4x+6)=-32+22 | | x^2+20x+70=6 | | Y=7+3x(-4) | | ysquared=1.44 | | 2(x+9)-15= | | Y=7+3-4 | | 3x+13=7x+21 | | 5f+6=8(f+12) | | 12x=9.2 | | 3p+19=-12 | | -13+15u=17u+17 | | x=-y+30 | | 8+3d=2d+1 | | 5x^3(6x^2+8x-17)=0 | | 6x^2-4x+29=0 | | -v+10=4v |